Neuro-Immune Interactions in Inflammation and Autoimmunity - Valentin A. Pavlov (Frontiers Research Topics, 2018)
The nervous system plays an important role in the regulation of immunity and inflammation. On the other hand unbalanced immune responses in inflammatory and autoimmune conditions may have a deleterious impact on neuronal integrity and brain function. Recent studies have characterized neural pathways communicating peripheral inflammatory signals to the CNS, and brain- and spinal cord-derived circuitries controlling various innate and adaptive immune responses and inflammation. A prototypical neural reflex circuit that regulates immunity and inflammation is the vagus nerve-based "inflammatory reflex". Ongoing research has revealed cellular and molecular mechanisms underlying these neural circuits and indicated new therapeutic approaches in inflammatory and autoimmune disorders. Pharmacological and bioelectronic modulation of neural circuitry has been successfully explored in preclinical settings of sepsis, arthritis, inflammatory bowel disease, obesity-driven disorders, diabetes and other diseases. These studies paved the way to successful clinical trials with bioelectronic neuronal modulation in rheumatoid arthritis and inflammatory bowel disease. Dysregulated release of cytokines and other inflammatory molecules may have a severe impact on brain function. Brain inflammation (neuroinflammation), imbalances in brain neuronal integrity and neurotransmitter systems, and cognitive impairment are characteristic features of post-operative conditions, sepsis, liver diseases, diabetes and other disorders characterized by immune and metabolic dysregulation. Derangements in cytokine release also play a pivotal role in depression. Characteristic brain reactive antibodies in autoimmune conditions, including systemic lupus erythematosus and neuromyelitis optica, significantly contribute to brain pathology and cognitive impairment. These studies, and the simultaneous characterization of neuro-protective cytokines, identified new therapeutic approaches for treating neurological complications in inflammatory and autoimmune disorders. This Frontiers Research Topic is a forum for publishing research findings and methodological and conceptual advances at the intersection of immunology and neuroscience. We hope that presenting new insight into bi-directional neuro-immune communication in inflammation and autoimmunity will foster further collaborations and facilitate the development of new efficient therapeutic strategies.